EVALUASI IMPLEMENTASI KEBIJAKAN SMART CITY DI KOTA MANADO (Evaluation of Smart City Policy Implementation in Manado City) - Stenly Beteng; Gene H. M. Kapantow; Pingkan P. Egam (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to evaluate the implementation of Smart City policies in Manado City. The research was carried out in January-July 2021. The data used were primary and secondary data. Primary data were obtained through in-depth interviews with informants who have a direct role in the implementation of the Manado Smart City policy. Secondary data were obtained through the study of documents and archives related to the implementation of Smart City Policies. The research variables used were taken from the results of the final evaluation of 96 programs included in the 6 dimensions of the Smart City of Manado City. The analytical method used was interactive data analysis through 4 stages, namely data collection, data reduction, data display and conclusions. For the analysis stage, it was focused on the final evaluation of the achievements of the Smart City program in Manado City. The results showed that the compliance of the implementor in implementing the Smart City program was not completely in accordance with the objectives of the Smart City Masterplan. The six dimensions of Smart City owned by Manado City contained 96 activity programs spread across various OPDs. Out of this 96 activities, there were 28 of them that had not been realized, and there were 35 others that had not been successfully implemented according to the indicators of success. Communication was an inhibiting factor in the implementation of the Smart City policy in Manado City, while resources, disposition and bureaucratic structure were the driving factors.